SI‐CLP inhibits the growth of mouse mammary adenocarcinoma by preventing recruitment of tumor‐associated macrophages - Yin, Shuiping; Wang, Nan; Riabov, Vladimir; Mossel, Dieuwertje M.; Larionova, Irina; Schledzewski, Kai; Trofimova, Olga; Sevastyanova, Tatyana; Zajakina, Anna; Schmuttermaier, Christina; Gratchev, Alexei; Flatley, Andrew; et al. (International journal of cancer, 2020)
What's new? Chitinase‐like proteins possess cytokine‐like properties and can manipulate cancer progression. Here the authors show that stabilin‐1 interacting chitinase‐like protein (SI‐CLP) inhibits ...